Understanding resilience in sustainable development: rallying call or siren song? - Park, AS (Wiley, 2023)
This article asks how the concept of resilience has been used in development studies. Set amidst the rise of resilience in sustainable development, it offers insights for scholars and policymakers, alike. Sampling 419 journal articles from 2017 to 2022, it uses Kuhnian paradigms to analyse development knowledge production on resilience. This produces three key findings. First is the absence of a coherent resilience paradigm (with shared definitions, problems and methods) in development studies. Second is its use, instead, by incumbent development paradigms in piecemeal fashion to extend and/or repackage pre-existing arguments. Third are ensuing possibilities for resilience as both a rallying call and siren song in sustainable development. Ultimately, resilience-based research and policy discourses open vital space for collective action across interdisciplinary and international divides. However, a lack of critical awareness of its non-uniform use can produce more harm than help. If the language of resilience is to advance collective prospects for development cooperation and climate action, then it will help to know precisely what we each are talking about.